Perception Gap in Migration Governance: A Comparative Analysis of Institutional and Migrant Assessments of R.A. 10022 - Emil Arca (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2026)
Despite the enactment of Republic Act No. 10022 to strengthen the protection of overseas Filipino workers, limited empirical evidence has compared institutional assessments with migrant workers experiences of policy implementation. This study evaluates the implementation of Republic Act No. 10022 in the Kingdom of Saudi Arabia by comparing the assessments of migrant workers and diplomatic personnel involved in migration governance. Using survey data from 200 respondents, consisting of 156 migrant workers and 44 diplomatic staff, the study examined four implementation domains: employment, recruitment, deployment, and services. Findings indicate that while both groups generally viewed the law’s implementation positively, diplomatic personnel consistently reported higher ratings than migrant workers. Independent-samples t-tests were performed using the aggregated weighted mean scores of the five indicators within each implementation domain to compare the assessments of diplomatic personnel and migrant workers. Statistical analysis revealed significant differences (p < .05) across all domains. The largest disparity was observed in deployment (t=18.76), indicating a substantial divergence between institutional assessments and migrant experiences. Lower ratings in employment and services further indicate a concentration of concerns in administrative efficiency, accessibility, and service responsiveness. The results demonstrate that governance effectiveness requires more than institutional performance indicators, as positive administrative evaluations may not reflect beneficiary experiences. By providing empirical evidence on the gap between official assessments and migrant perceptions, the study contributes to migration governance literature and emphasizes the necessity of integrating user-centered evaluation into the implementation of migrant protection policies.